Proyecto Centro : vivienda, comercio y oficinas (2018)
"The town of La Candelaria, is bounded by the San Francisco and San Agustín rivers, located in a privileged place in the city, is the smallest and oldest in Bogota, with a population of 25,000 inhabitants and is characterized as the administrative center , educational and cultural of the capital, which makes it a great opportunity for action to develop an architectural project like the one proposed. The project aims to solve four main problems given by the place, First, cover the housing needs required by the high floating population that the sector has. Second, to generate ample and porous public space for the recreation and enjoyment of its inhabitants, to activate local commerce creating spaces for its development and to create work spaces that generate activity in the area."--Tomado del Formato de Documento de Grado.